2020
DOI: 10.1128/mra.00387-20
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Citrobacter freundii UFMG-H9, Isolated from Urine from a Healthy Bovine Heifer (Gyr Breed)

Abstract: Citrobacter freundii is a pathogen associated with antibiotic resistance and severe infections in humans. Here, we report the draft genome sequence of C. freundii strain UFMG-H9, an isolate from urine from a healthy Gyr heifer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The human UT microbiota is the best studied UT microbiota amongst mammals. Isolation of strains from the bovine UT, including our prior work investigating other bacterial taxa ( Giannattasio-Ferraz et al, 2020a , b , c , d , e , 2021a ) and our study presented here, is a further step toward understanding the healthy bovine UT microbiota. Furthermore, here we have compared these bovine isolates to human UT isolates, producing the first examination of urinary bacteria and urinary phages from two different mammals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The human UT microbiota is the best studied UT microbiota amongst mammals. Isolation of strains from the bovine UT, including our prior work investigating other bacterial taxa ( Giannattasio-Ferraz et al, 2020a , b , c , d , e , 2021a ) and our study presented here, is a further step toward understanding the healthy bovine UT microbiota. Furthermore, here we have compared these bovine isolates to human UT isolates, producing the first examination of urinary bacteria and urinary phages from two different mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Based upon the 16S rRNA gene sequence, four isolates from four different animals were identified as P. aeruginosa and five isolates, from the same four animals, were identified as E. coli . Isolates of other taxa have been described elsewhere ( Giannattasio-Ferraz et al, 2020a , b , c , d , e , 2021a , b ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that C. phoceense has been primarily detected within the urinary tract of humans and now cattle suggests that this species may be specific to this environment. Recent studies have found that some of the same bacterial species inhabit both the bovine and human urinary microbiota [48,49]. Previous research found that the proteoglycan surface within the human and bovine bladder are similar [50]; in humans, this layer is a source for adhesion and nutrients by urinary bacteria [51].…”
Section: Discussionmentioning
confidence: 99%